The genetics of circulating BDNF: towards understanding the role of BDNF in brain structure and function in middle and old ages. Issue 2 (28th October 2020) - Li, Shuo; Weinstein, Galit; Zare, Habil; Teumer, Alexander; Völker, Uwe; Friedrich, Nele; Knol, Maria J; Satizabal, Claudia L; Petyuk, Vladislav A; Adams, Hieab H H; Launer, Lenore J; Bennett, David A; et al.
Abstract: Brain-derived neurotrophic factor (BDNF) plays an important role in brain development and function. Substantial amounts of BDNF are present in peripheral blood, and may serve as biomarkers for Alzheimer's disease incidence as well as targets for intervention to reduce Alzheimer's disease risk. With the exception of the genetic polymorphism in the BDNF gene, Val66Met, which has been extensively studied with regard to neurodegenerative diseases, the genetic variation that influences circulating BDNF levels is unknown. We aimed to explore the genetic determinants of circulating BDNF levels in order to clarify its mechanistic involvement in brain structure and function and Alzheimer's disease pathophysiology in middle-aged and old adults. Thus, we conducted a meta-analysis of genome-wide association study of circulating BDNF in 11 785 middle- and old-aged individuals of European ancestry from the Age, Gene/Environment Susceptibility-Reykjavik Study (AGES), the Framingham Heart Study (FHS), the Rotterdam Study and the Study of Health in Pomerania (SHIP-Trend). Furthermore, we performed functional annotation analysis and related the genetic polymorphism influencing circulating BDNF to common Alzheimer's disease pathologies from brain autopsies. Mendelian randomization was conducted to examine the possible causal role of circulating BDNF levels with various phenotypes including cognitive function, stroke, diabetes, cardiovascular disease, physical activity and diet patterns. Gene interaction networks analysis was also performed. The estimated heritability of BDNF levels was 30% (standard error = 0.0246, P -value = 4 × 10 −48 ). We identified seven novel independent loci mapped near the BDNF gene and in BRD3, CSRNP1, KDELC2, RUNX1 (two single-nucleotide polymorphisms) and BDNF-AS . The expression of BDNF was associated with neurofibrillary tangles in brain tissues from the Religious Orders Study and Rush Memory and Aging Project (ROSMAP). Seven additional genes ( ACAT1, ATM, NPAT, WDR48, TTC21A, SCN114 and COX7B ) were identified through expression and protein quantitative trait loci analyses. Mendelian randomization analyses indicated a potential causal role of BDNF in cardioembolism. Lastly, Ingenuity Pathway Analysis placed circulating BDNF levels in four major networks. Our study provides novel insights into genes and molecular pathways associated with circulating BDNF levels and highlights the possible involvement of plaque instability as an underlying mechanism linking BDNF with brain neurodegeneration. These findings provide a foundation for a better understanding of BDNF regulation and function in the context of brain aging and neurodegenerative pathophysiology. Abstract : Thirty per cent of variation in circulating BDNF levels appears heritable. Loci adjacent to the BDNF gene and in BRD3, CSRNP1, KDELC2, RUNX1 and BDNF-AS influence levels. Using Ingenuity Pathway Analysis, these genes implicate major networks. Mendelian randomization suggests a role for BDNF in cardioembolism and BDNF expression associates with fewer neurofibrillary tangles. Graphical Abstract: